The use of the technologies of information and comunication for the professional teachment - Mayta Huatuco, Rosmeri (2009)
The aim of this paper is to answer the following question: For ICTs to be used in vocational education?. As a first initial step is the integration of ICT in the teaching process, the continuous training of teachers in three areas: pedagogy, management and computer literacy, integrate ICT in the Curriculum and training via ICT. The study involves an analysis of access to ICTs by region in the world, Latin America and Peru, where he found that in North America the percentage of Internet users was 74.2% and that has a lower percentage of users is Africa with 6.8%, there is a large gap. Has the greatest percentage of users in Latin America is Chile with 50.4% Percentage of households with ICTs in Peru is 7.6% on the Internet, cell phone 60%, 18.9% in cable TV and 29% in fixed telephony.